Mechanisms of the communication process between the student and the teacher at the university stage - BENMICIA, Rafika (Journal of Human Sciences, 2025)
Modern educational curricula, taking advantage of the various ideas and concepts contained in the linguistic theories and various pedagogical approaches adopted by modern educational reforms, emphasize the need to change the function of each element of the communication process. (Professor), interlocutor (students), university educational discourse as the university professor should be convinced (Arabic) His role in the education process has gone beyond the threshold of the idea of dropping off and stuffing information. In his mind, he must be deeply convinced that his role as President is to guide, guide, foster dialogue among students and create a spirit of cooperation among them in various communication situations. Conversely, it should not take hold in the students’ mind that it is a mere recipient of information. incapable of discussing them, but should be convinced that he possesses diverse competencies that make him capable of dialogue and discussion in every communicative situation. At the same time, university educational discourse should be meaningful and contain the contents of the convergence of university students’ realities. The success of the communication process is accompanied by a change in each component’s endeavor and also by the activation of its mechanisms and the removal of them from the limits of the model.